The responses of poplars to fungal pathogens: A review of the defensive pathway - Zeng, Yi; Song, Haifeng; Xia, Linchao; Yang, Le; Zhang, Sheng (Frontiers in Plant Science, 2023)
Long-lived tree species need to cope with changing environments and pathogens during their lifetime. As model system for woody plants, poplars are also hosts of a large variety of fungus, which cause serious damage to the growth and forest nurseries. Poplar defensive responses are generally associated with the fitness of fungus and life cycle of fungus, therefore, the defense strategies of poplar against necrotrophic and biotrophic fungus are different. Poplar initiates constitutive defenses and inducible defenses based on recognition of the fungus, hormone signaling network cascades, activation of defense-related genes and transcription factors and production of phytochemicals. The means of sensing fungus invasion in poplars are similar with herbs, both of which are mediated by receptor proteins and resistance (R) proteins, leading to pattern-triggered immunity (PTI) and effector-triggered immunity (ETI), but poplars have evolved some unique defense mechanisms compared with Arabidopsis due to their longevity. In this paper, current research on poplar defensive responses to necrotrophic and biotrophic fungus, which mainly include the physiological and genetic aspects, and the role of noncoding RNA (ncRNA) in fungal resistance are reviewed. This review also provides strategies to enhance poplar disease resistance and some new insights into future research directions.